Pełzanie Metali i Obliczanie Pełzania - Rabotnow, Ju.N. (Engineering Transactions, 1960)
The author gives a survey of various creep theories used for the computation of structures working at high temperatures.The conditions are analyzed under which steady-state creep takes place.The notion of quasi-steady-state creep is introduced in which the stresses are unknown and the strain rates are not constant. It is seen that in a number of machine design problems the most simple computation methods lead to sufficiently accurate results and may constitute a basis for strength determination. This statement is illustrated by experimental data from the destruction tests of rotating discs. A computation based on the creep theory enables us to foretell in a comparatively accurate manner the destruction. The author gives some computation methods of discs on the basis of the theory of strain-hardening taking the stress-distribution into consideration, which is particularly important for the analysis of non-steady states. Also the stability problem under the conditions of creep is considered. The stability loss of a compressed bar is analyzed on the basis of the inheritance theory presented previously by the author.